2020
DOI: 10.1002/smi.2942
|View full text |Cite
|
Sign up to set email alerts
|

Brief mindfulness session improves mood and increases salivary oxytocin in psychology students

Abstract: Mindfulness-based interventions (MBI) have been shown to be effective in increasing empathy in health professionals. Yet, more research is needed to analyse the specific influence of mindfulness exercises on biological variables involved in empathy, such as the biological system of oxytocin activity. In this study, we analyse the effects of a brief mindfulness session on positive and negative affect, state anxiety and salivary oxytocin (sOXT) in psychology students (N = 68). In the experimental group (n = 42),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 64 publications
(97 reference statements)
2
38
0
Order By: Relevance
“…Although both instruments are designed on the basis of factor analyses of the most commonly used questionnaires in both constructs and have sufficient psychometric guarantees, some authors point out deficiencies in them such as the influence of subjective perception or problems in establishing real change. Thus, situational assessments or the use of biological markers for empathy (Bellosta-Batalla et al, 2017;Breithaupt, 2009) or objective monitoring (Quintana and Rivera, 2012) and the use of behavioral measures of mindfulness practice (Grossman, 2011) are proposed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although both instruments are designed on the basis of factor analyses of the most commonly used questionnaires in both constructs and have sufficient psychometric guarantees, some authors point out deficiencies in them such as the influence of subjective perception or problems in establishing real change. Thus, situational assessments or the use of biological markers for empathy (Bellosta-Batalla et al, 2017;Breithaupt, 2009) or objective monitoring (Quintana and Rivera, 2012) and the use of behavioral measures of mindfulness practice (Grossman, 2011) are proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found gender differences in the influence of mindfulness on other constructs such as aggression or rumination (Peters et al, 2015;Eisenlohr-Moul et al, 2016) so the role of gender as a moderator in the effects of mindfulness on empathy will be explored. In recent years, mindfulness-based interventions have been proposed as a means to improve empathy responses (Fulton and Cashwell, 2015;Kemper and Khirallah, 2015;Foukal et al, 2016;Lamothe et al, 2016;Bellosta-Batalla et al, 2017). Empathy involves the ability to understand and share the feelings of others.…”
Section: Introductionmentioning
confidence: 99%
“…After a MBI, participants also improved in terms of bias towards negative emotional stimuli, while emotion processing in general was decreased [86]. Participants of a brief MBI also showed significant decreases in negative affect and state anxiety [87], as well as increased positive affect and a reduction of subjectively perceived stress that was linked to decreases in cortisol levels [88]. Neuroimaging studies furthermore revealed structural and functional alterations associated with mindfulness meditation training.…”
Section: Stress and Negative Affectmentioning
confidence: 92%
“…On the other hand, Bellosta-Batalla et al (2020), evaluated the impact of a brief mindfulness session on mood and salivary OXT in psychology students. They found an increase in OXT levels in group received intervention, as well as a reduction in negative affect and anxiety.…”
Section: Others Stimulus Associated To Oxt Secretionmentioning
confidence: 99%